Perovskite solar cell and preparation method and application thereof
By introducing an inorganic nanoparticle buffer layer into perovskite solar cells, the electron shunt problem in perovskite solar cells is solved, the filling factor and open circuit voltage are improved, the photoelectric conversion efficiency and stability are enhanced, and it is suitable for large-scale production.
Patent Information
- Application Number
- CN202411261578.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-27
AI Technical Summary
The existing perovskite solar cells cause the metal electrodes to come into direct contact with the perovskite film due to pinholes or defects in the electron transport layer, causing electron shunts, reducing the filling factor and open circuit voltage, and thus affecting the photoelectric conversion efficiency.
A buffer layer composed of inorganic nanoparticles is introduced into a perovskite solar cell, which is located between the perovskite light absorption layer and the electron transport layer, preventing metal ions from migration, suppressing electron shunts, and forming an energy level gradient to improve electron transport efficiency.
It effectively improves the filling factor and open circuit voltage of perovskite solar cells, enhances charge transfer efficiency and stability, reduces energy loss, and is suitable for large-scale production.
Smart Images

Figure CN119212407A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a perovskite solar cell and a preparation method and application thereof. Background Art
[0002] The structure of a trans-structured perovskite solar cell usually includes a transparent electrode, a hole transport layer, a perovskite layer, an electron transport layer, and a metal electrode. The material of the electron transport layer usually includes PCBM or C60, etc. The extremely thin electron transport layer formed by these materials may have pinholes or defects, which will lead to direct contact between the metal electrode and the perovskite film. This direct contact will form a "shunt channel" that allows electrons to bypass the normal path of the photocurrent and flow directly to the metal electrode, resulting in a reduction in the fill factor (FF) and open circuit voltage (Voc) of the trans-structured perovskite solar cell. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a perovskite solar cell, which can effectively improve the fill factor and open circuit voltage of the perovskite solar cell, and ultimately improve its photoelectric conversion efficiency.
[0004] The present invention also provides a method for preparing the perovskite solar cell.
[0005] The present invention also provides applications of the perovskite solar cell.
[0006] According to an embodiment of the first aspect of the present invention, a perovskite solar cell is provided, wherein the perovskite solar cell comprises a transparent electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal electrode which are sequentially stacked; the perovskite solar cell further comprises a buffer layer arranged between the perovskite light absorption layer and the electron transport layer;
[0007] The buffer layer includes inorganic nanoparticles, and the material of the inorganic nanoparticles includes at least one of aluminum oxide, vanadium oxide, sodium sulfide and silicon oxide.
[0008] The perovskite solar cell according to the embodiment of the present invention has at least the following beneficial effects:
[0009] In perovskite solar cells, the migration of metal ions may lead to degradation of cell performance and stability problems. The buffer layer can effectively inhibit this migration and protect the stability of the perovskite light absorption layer.
[0010] (2) The buffer layer is located between the perovskite light absorption layer and the external environment, which can block the erosion of harmful substances such as moisture and oxygen and protect the chemical stability of the perovskite light absorption layer.
[0011] (3) The buffer layer can effectively isolate the device from intrinsic and extrinsic stress sources without sacrificing electrical and optical properties, forming an interface package and improving device stability.
[0012] (4) The buffer layer can fill the microscopic gaps between the perovskite light absorption layer and the electron transport layer, making the contact between the two layers closer and smoother. Good interface conformality helps reduce interface resistance and improve charge transfer efficiency.
[0013] (5) Non-radiative recombination loss is one of the important sources of energy loss in photovoltaic cells. The buffer layer can reduce this loss and improve the photoelectric conversion efficiency of perovskite solar cells.
[0014] (6) The buffer layer can also effectively suppress electron shunting, ensuring that electrons can be smoothly transferred from the perovskite light absorption layer to the electron transport layer, thereby reducing energy loss.
[0015] (7) The buffer layer forms an energy level gradient on the electron transmission path. This gradient can guide the electrons to transmit in a specific direction and reduce the scattering and loss of electrons during the transmission process. The existence of the energy level gradient also helps to improve the mobility of electrons and further speed up the transmission speed of electrons.
[0016] In summary, in the perovskite solar cell provided by the present invention, a buffer layer is added between the electron transport layer and the perovskite light absorption layer, which can form an energy level gradient on the electron transport path without sacrificing the electrical and optical properties of the perovskite solar cell, thereby promoting electron transport; inhibiting metal ion migration, protecting the perovskite light absorption layer, inhibiting or even preventing the chemical reaction between the metal electrode and the perovskite light absorption layer, blocking water molecules, oxygen and other substances in the environment from damaging the perovskite light absorption layer, and improving the stability of the battery.
[0017] According to some embodiments of the present invention, the perovskite solar cell further comprises a transparent substrate, which is disposed on a surface of the transparent electrode away from the perovskite light absorbing layer, thereby providing support and preventing the perovskite solar cell from breaking during preparation and use.
[0018] According to some embodiments of the present invention, the transparent electrode includes at least one of ITO and FTO. In actual production, the transparent electrode and the transparent substrate are integrated together, for example, it can be ITO glass or FTO glass.
[0019] According to some embodiments of the present invention, the material of the hole transport layer includes at least one of VNPB (CAS: 1010396-31-2), NiOx, MEO-2PACZ (CAS: 2377770-18-6), ME-4PACZ (CAS: 2747959-96-0), 2PACZ (20999-38-6), PTAA (CAS: 1333317-99-9) and P3HT (CAS: 104934-50-1).
[0020] According to some embodiments of the present invention, the thickness of the hole transport layer is 5-15 nm, for example, about 8 nm, 10 nm or about 12 nm.
[0021] According to some embodiments of the present invention, the components of the perovskite light absorbing layer include ABX3; wherein A includes Cs, FA and MA or at least one thereof; B includes Pb; and X includes at least one of Br and Cl. More specifically, the components of the perovskite light absorbing layer include FA x Cs 1–x PbI3, FAMACsPbI3 and (FA a MA 1-a ) y Cs 1-y Pb(I z Br 1-z ) at least one of 3.
[0022] According to some embodiments of the present invention, the thickness of the perovskite light absorbing layer is 300-600 nm, for example, about 400 nm, 450 nm or about 500 nm.
[0023] According to some embodiments of the present invention, the thickness of the buffer layer is 30-100 nm, for example, about 30 nm, 40 nm, 50 nm, 60 nm or about 100 nm.
[0024] According to some embodiments of the present invention, the particle size of the inorganic nanoparticles in the buffer layer is 10-30 nm, for example, about 20 nm or about 25 nm.
[0025] According to some embodiments of the present invention, the material of the electron transport layer includes C 60 , SnO2, BCP and PCBM.
[0026] According to some embodiments of the present invention, the material of the electron transport layer is one of the following combinations:
[0027] C 60 and SnO2, C 60and BCP, PCBM and SnO2, PCBM and BCP.
[0028] According to some embodiments of the present invention, the electron transport layer includes a C layer stacked from the buffer layer. 60 layer and SnO2 layer. Among them,
[0029] C 60 The thickness of the layer is 20 to 30 nm; for example, it may be about 25 nm;
[0030] The thickness of the SnO2 layer is 5 to 30 nm; for example, it can be about 10 nm, 15 nm, 20 nm or about 25 nm.
[0031] According to some embodiments of the present invention, the electron transport layer includes a PCBM layer and a BCP layer stacked and arranged starting from the buffer layer.
[0032] The thickness of the PCBM layer is 30 to 50 nm; for example, it may be about 35 nm, 40 nm or about 45 nm;
[0033] The thickness of the BCP layer is 5 to 30 nm; for example, it may be about 10 nm, 15 nm, 20 nm or about 25 nm.
[0034] According to some embodiments of the present invention, the material of the metal electrode includes at least one of gold, silver, copper, and bismuth. When the number of the material types included is ≥ 2, the metal electrode can be a single layer containing multiple metals (i.e., the metal exists in the form of its alloy); the metal electrode can also be multiple layers, such as a silver layer and a copper layer stacked together.
[0035] According to some embodiments of the present invention, the thickness of the metal electrode is 100-150 nm, for example, about 110 nm, 120 nm, 130 nm or about 140 nm.
[0036] According to an embodiment of the second aspect of the present invention, a method for preparing the perovskite solar cell is provided, and the method comprises the following steps:
[0037] S1. Disposing the hole transport layer on the surface of the transparent electrode;
[0038] S2. Disposing the perovskite light absorbing layer on the surface of the hole transport layer;
[0039] S3. Disposing the buffer layer on the surface of the perovskite light absorbing layer by a liquid phase method;
[0040] S4. Arrange the electron transport layer and the metal electrode in sequence on the surface of the buffer layer.
[0041] Since the preparation method adopts all the technical solutions of the perovskite solar cell in the above embodiment, it at least has all the beneficial effects brought by the technical solutions in the above embodiment.
[0042] The present invention adopts a liquid phase method to set the buffer layer. Compared with the traditional dry deposition method such as ALD, it does not require high temperature treatment, thus avoiding phase transfer and chemical decomposition during high temperature treatment; it does not require complex equipment and operation, and takes a short time; thus, the area of the perovskite solar cell can be enlarged to achieve batch preparation. This preparation method is simple, efficient, and suitable for large-scale production.
[0043] According to some embodiments of the present invention, step S1 further includes cleaning the transparent electrode before providing the hole transport layer.
[0044] According to some embodiments of the present invention, the cleaning method includes UV-O3 treatment.
[0045] According to some embodiments of the present invention, the cleaning time is 15 to 25 minutes, for example, about 20 minutes.
[0046] According to some embodiments of the present invention, in step S1, the method for setting the hole transport layer includes coating a hole transport layer slurry on the surface of the transparent electrode and annealing the hole transport layer.
[0047] According to some embodiments of the present invention, the solute of the hole transport layer slurry includes VNPB.
[0048] According to some embodiments of the present invention, the solvent of the hole transport layer slurry includes at least one of CB (chlorobenzene, CAS: 108-90-7), IPA (isopropyl alcohol, CAS: 67-63-0), DMF (N,N-dimethylformamide, CAS: 68-12-2) and EtOH (ethanol, CAS: 64-17-5).
[0049] According to some embodiments of the present invention, the concentration of the hole transport layer slurry is 1-2 mg / mL, for example, about 1.5 mg / mL.
[0050] According to some embodiments of the present invention, the hole transport slurry is coated by spin coating, wherein the spin coating speed is 5500-6500 rpm, for example, it can be about 6000 rpm, and the spin coating time is 25-35 seconds, for example, it can be about 30 seconds.
[0051] According to some embodiments of the present invention, the annealing temperature of the hole transport layer is 100-150° C., for example, about 110° C., 120° C., 130° C. or about 140° C.
[0052] According to some embodiments of the present invention, the annealing time of the hole transport layer is 15 to 25 minutes, for example, about 20 minutes.
[0053] According to some embodiments of the present invention, in step S2, the method for setting the perovskite light absorption layer includes coating a perovskite slurry on the surface of the hole transport layer and performing perovskite annealing.
[0054] According to some embodiments of the present invention, the solute of the perovskite slurry includes FA x Cs 1–x PbI3, FAMACsPbI3 and (FA a MA 1-a ) y Cs 1-y Pb(I z Br 1-z )3, for example, may be some or all of CsI, FAI, MABr, PbI2, PbBr2, MACl. The specific amount of addition is determined by the target material of the perovskite light absorbing layer.
[0055] According to some embodiments of the present invention, the solvent of the perovskite slurry includes DMF and DMSO, wherein the volume ratio of DMF to DMSO is 4 to 8:1, for example, about 5:1, 6:1 or about 7:1.
[0056] According to some embodiments of the present invention, the concentration of the perovskite slurry is 1.3-1.8 mol / mL, for example, about 1.4 mol / mL, 1.5 mol / mL, 1.6 mol / mL or about 1.7 mol / mL.
[0057] According to some embodiments of the present invention, the coating method of the perovskite slurry includes spin coating. The rotation speed of the spin coating is 3500-4500 rpm. For example, it can be about 4000 rpm. The duration of the spin coating is 30-40 seconds. For example, it can be about 35 seconds.
[0058] According to some embodiments of the present invention, step S2 further includes adding an anti-solvent to the surface of the perovskite slurry at 15 to 25 seconds (for example, about 18 seconds, 20 seconds, 22 seconds, 23 seconds or about 24 seconds) of spin coating the perovskite slurry. The anti-solvent includes chlorobenzene, ethyl acetate, ether, and phenol. The amount of the anti-solvent is 10 to 15 μL / cm 2 For example, it can be about 12 μL / cm 2 . or about 13μL / cm 2 Thus, the anti-solvent can be fully spread by means of the spin coating process of the perovskite slurry.
[0059] According to some embodiments of the present invention, the perovskite annealing temperature is 100-110° C., for example, specifically about 105° C.
[0060] According to some embodiments of the present invention, the perovskite annealing time is 20 to 30 minutes, for example, about 25 minutes.
[0061] According to some embodiments of the present invention, in step S3, the liquid phase method includes coating a buffer layer slurry on the surface of the perovskite light absorbing layer and then annealing.
[0062] According to some embodiments of the present invention, the buffer layer slurry includes the inorganic nanoparticles and a dispersant.
[0063] According to some embodiments of the present invention, the dispersant includes isopropanol, ethanol, water, butyl acetate and propylene glycol methyl ether acetate (PMA, CAS: 108-65-6). The dispersant selected by the present invention is cheap, and the spraying or spin coating process is simple, and does not require complicated equipment and operation, which further reduces the production cost. The inorganic particle nanoparticles and dispersant in the buffer layer are environmentally friendly materials and meet the requirements of green production.
[0064] According to some embodiments of the present invention, the concentration of the buffer layer slurry is 0.5-2 mg / mL, for example, about 0.8 mg / mL, 1.0 mg / mL, 1.2 mg / mL, 1.4 mg / mL or about 1.5 mg / mL.
[0065] According to some embodiments of the present invention, the preparation method of the buffer layer slurry includes first dispersing the inorganic nanoparticles in part of the dispersant to obtain a preliminary dispersion, and then mixing and diluting with the remaining dispersant. This can improve the dispersion uniformity of the buffer layer slurry. The concentration of the preliminary dispersion is 15 to 25 wt %; for example, it can be about 20 wt %.
[0066] According to some embodiments of the present invention, the volume ratio of the preliminary dispersion to the buffer layer slurry is 1:4 to 200. For example, it can be about 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:70, 1:75, 1:80, 1:90, 1:100, 1:110, 1:120, 1:150 or about 1:180.
[0067] According to some embodiments of the present invention, the buffer layer slurry coating method includes at least one of spin coating and spray coating, thereby improving the efficiency and photothermal stability of large-area battery preparation.
[0068] According to some embodiments of the present invention, when the buffer layer slurry is coated by spin coating, the spin coating speed is 4500-5500 rpm; for example, it can be about 5000 rpm; the spin coating time is 25-35 s; for example, it can be about 30 s.
[0069] According to some embodiments of the present invention, the annealing temperature is 90-110° C., for example, specifically about 100° C.
[0070] According to some embodiments of the present invention, the annealing time is 8 to 12 minutes, for example, about 10 minutes.
[0071] According to some embodiments of the present invention, in step S4, the electron transport layer is provided by at least one of evaporation and ALD.
[0072] Wherein, when the material of the electron transport layer is selected from C 60 When the electron transport layer is provided by evaporation.
[0073] When the material of the electron transport layer is selected from metal oxide, the method for setting the electron transport layer is ALD.
[0074] According to some embodiments of the present invention, in step S4, the method for disposing the metal electrode includes evaporation, wherein the evaporation specifically includes a first stage evaporation and a second stage evaporation performed sequentially.
[0075] The deposition rate of the metal electrode in the first stage of evaporation is For example, it can be about
[0077] In the first stage of evaporation, the deposition thickness of the metal electrode is 8-12 nm; for example, it can be about 10 nm.
[0078] In the first stage of evaporation, the vacuum degree of the environment is ≤1×10 -4 Pa.
[0079] The deposition rate of the metal electrode in the second stage of evaporation is For example, it can be about
[0081] The second stage of evaporation deposits the metal electrode to a target thickness.
[0082] In the second stage of evaporation, the vacuum degree of the environment is ≤5×10 -4 Pa.
[0083] According to an embodiment of the third aspect of the present invention, there is provided application of the preparation method in surface photovoltaics, space photovoltaics and wearable devices.
[0084] Since the application adopts all the technical solutions of the perovskite solar cell of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment.
[0085] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0086] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0087] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0089] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell obtained in an embodiment of the present invention.
[0090] Figure 2 It is a JV curve diagram of the perovskite solar cells obtained in the examples of the present invention and the comparative examples.
[0091] Figure 3 It is a stability test diagram of the constant temperature and humidity system of the perovskite solar cells obtained in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0092] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0093] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0094] Example 1
[0095] refer to Figure 1 The structure shown in this example is a perovskite solar cell prepared in the following specific steps:
[0096] S1. The integrated structure of the transparent substrate and the transparent electrode is made of commercial FTO glass, which is treated with UV-O3 for 20 minutes and then used; the area is 5×5cm 2 ;
[0097] Setting a hole transport layer: spin coating a hole transport layer slurry on a surface of one side of the FTO layer of the FTO glass and then annealing the hole transport layer;
[0098] In this step, the hole transport slurry was a 1.5 mg / mL VNPB solution in CB with a volume of 300 μL;
[0099] The spin coating condition was 6000 rpm / 30 s;
[0100] The annealing condition of the hole transport layer is 120°C / 20min.
[0101] The thickness of the obtained hole transport layer was about 15 nm.
[0102] S2. The method for setting the perovskite light absorption layer is as follows:
[0103] 300 μL of perovskite slurry was spin-coated onto the surface of the hole transport layer and the perovskite was annealed.
[0104] The composition of the perovskite slurry is (FA 0.92 MA 0.08 ) 0.95 Cs 0.05 Pb(I 0.92 Br 0.08 )3, concentration is 1.6 mol / mL, solvent is DMF:DMSO=5:1 (volume ratio);
[0105] The spin coating condition of the perovskite slurry was 4000 rpm / 35 s, and 300 μL of chlorobenzene antisolvent was added at 22 s;
[0106] The perovskite annealing conditions were annealing at 105 °C for 25 min;
[0107] The thickness of the resulting perovskite light absorbing layer was about 450 nm.
[0108] S3. Set the buffer layer:
[0109] 150 μL of buffer layer slurry was coated on the surface of the perovskite absorption layer and then annealed.
[0110] The buffer layer slurry is nano-alumina dispersion slurry (CAS: 1344-28-1, 30nm particle size, isopropanol solution, aladdin), with a concentration of 1.4mg / mL:
[0111] The coating method was spin coating at 5000 rpm / 30 s;
[0112] The annealing condition is 100°C / 10min.
[0113] The thickness of the obtained buffer layer is about 30 nm.
[0114] S4. Setting up the electron transport layer:
[0115] In this example, the electron transport layer includes a C layer stacked from the buffer layer. 60 layer and SnO2 layer, among which C 60 The layer is set by evaporation with a thickness of 25 nm, and the SnO2 layer is set by ALD deposition with a deposition thickness of 20 nm.
[0116] Set up the metal electrode:
[0117] The metal electrode is set on the surface of the electron transport layer. The material is silver and the thickness is 120nm. The method is evaporation. The evaporation is carried out in two stages. First, the vacuum degree is less than 1*10 -4 Pa, the rate is stable at When the large baffle is opened, evaporation is started to a thickness of 10 nm. Then the power is increased and the vacuum in the evaporation chamber reaches 5×10 -4 After Pa, adjust the evaporator current or power to stabilize it The deposition rate was set to 0.100 nm, and the film thickness meter displayed 120 nm.
[0118] Example 2
[0119] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0120] In step S3, the composition of the buffer layer slurry is different;
[0121] In this example, the buffer layer slurry is an isopropanol dispersion of vanadium oxide nanoparticles (CAS: 12036-21-4, 20 nm particle size, aladdin) with a concentration of 1.5 mg / mL.
[0122] Example 3
[0123] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0124] In step S3, the composition of the buffer layer slurry is different;
[0125] In this example, the buffer layer slurry is an isopropanol dispersion of sodium sulfide nanoparticles (CAS: 1313-82-2, 30 nm particle size, aladdin) with a concentration of 2 mg / mL.
[0126] Example 4
[0127] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0128] In step S3, the composition of the buffer layer slurry is different;
[0129] In this example, the buffer layer slurry is an isopropanol dispersion of silicon oxide nanoparticles (CAS: 7631-86-9, 30 nm particle size, aladdin) with a concentration of 1.5 mg / ml.
[0130] Example 5
[0131] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0132] In step S2, the composition of the perovskite slurry is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3;
[0133] In step S4, the electron transport layer includes a PCBM layer and a BCP layer stacked and arranged starting from the buffer layer, wherein the PCBM layer is arranged by spin coating, the slurry concentration used is 20 mg / mL, the slurry dispersant is CB, and the thickness is 40 nm; the BCP layer is arranged by spin coating, the slurry concentration used is 1 mg / mL, the slurry dispersion is IPA, and the deposition thickness is 20 nm.
[0134] Comparative Example 1
[0135] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0136] This example does not include step S3.
[0137] Comparative Example 2
[0138] This example prepares a perovskite solar cell, which differs from Example 5 in that:
[0139] This example does not include step S3.
[0140] Comparative Example 3
[0141] This example prepares a perovskite solar cell, which differs from Example 1 in that:
[0142] In step S3, an ALD method is used to prepare a buffer layer made of aluminum oxide.
[0143] Using an atomic layer deposition system, at a substrate temperature of 90°C, TMA and water were used as precursors to deposit an Al2O3 layer with a thickness of about 30 nm after several cycles.
[0144] Test Case
[0145] This example tests the performance of the perovskite solar cells obtained in the examples and comparative examples. The specific testing method is as follows:
[0146] The test instruments and test conditions used in the examples are as follows:
[0147] JV curve: First, using a standard silicon solar cell (2×2cm 2 , SRC-00019) calibrated to the standard solar spectrum corresponding to 1sun (AM1.5G, 100mW / cm 2 ) corresponding to the current. Then, the device is placed under the calibrated test light source using a test fixture (performed in an N2 glove box), and the JV characteristic curve of the perovskite semiconductor optoelectronic device is automatically tested by the Keithley 2450 source meter and the corresponding configured software. The open circuit voltage (0pencircuitvoltage, VOC), short-circuit current density (Short-circuit density, JSC), fill factor (Fillfactor, FF) and photoelectric conversion efficiency (Power conversion efficiency, PCE) are obtained from the curve. The specific formula is as follows:
[0148] FF=Pmax / Voc×Jsc=Vmax×Jmax / Voc*Jsc, PCE=Pmax / Pin=Voc×Jsc×FF / Pin;
[0149] Among them, Pmax is the maximum output power, VOC and JSC are the voltage and current density at the maximum power point, and Pin is the incident light power.
[0150] During the JV curve test, the test voltage was set to 1.2V (start) to -0.2V (end), the interval was 0.02V, and the delay time was 0.1s.
[0151] The constant temperature and humidity test conditions are as follows: the temperature of the constant temperature and humidity test system is adjusted to 85°C and the humidity is adjusted to 85% RH. After the first test, the test is performed once every 100 hours.
[0152] The test results are shown in Table 1. Figures 2-3 shown.
[0153] Table 1 Performance of perovskite solar cells obtained in Examples and Comparative Examples
[0154]
[0155]
[0156] By comparing Examples 1 to 4, it can be seen that, within the scope provided by the present invention, adjusting the type of inorganic nanoparticles in the buffer layer can significantly improve the comprehensive performance of the obtained perovskite solar cell. In particular, when the inorganic nanoparticles are selected from sodium sulfide, the stability of the perovskite solar cell is more significantly improved.
[0157] By comparing Example 1 and Example 5, it can be seen that the buffer layer provided by the present invention is well matched with the perovskite light absorption layer and electron transport layer known in the industry, but the overall performance of the obtained perovskite solar cell will still be slightly affected by changes in the material.
[0158] By comparing Example 1 and Comparative Example 3, it can be seen that in the perovskite solar cell provided by the present invention, the buffer layer is set by wet coating, which has a wider application range than the conventional dry method such as ALD to set the buffer layer, and the obtained perovskite solar cell has better stability.
[0159] In summary, compared with the comparative example without a buffer layer, the perovskite solar cell provided by the embodiment of the present invention has a higher open circuit voltage, fill factor, photoelectric conversion efficiency and higher stability in use. This also shows that the buffer layer provided by the present invention has the functions of adjusting energy levels, suppressing electron shunting, reducing interface resistance and encapsulation layer. It is precisely because of the above-mentioned excellent effects that the perovskite solar cell provided by the present invention is expected to be widely used in surface photovoltaics, space photovoltaics and wearable devices.
[0160] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A perovskite solar cell, comprising a transparent electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal electrode arranged in a stacked manner; characterized in that: The perovskite solar cell further comprises a buffer layer disposed between the perovskite light absorption layer and the electron transport layer; The buffer layer includes inorganic nanoparticles, and the material of the inorganic nanoparticles includes at least one of aluminum oxide, vanadium oxide, sodium sulfide and silicon oxide.
2. The perovskite solar cell according to claim 1, characterized in that: The components of the perovskite light absorbing layer include FA x Cs 1–x PbI3, FAMACsPbI3 and (FA a MA 1-a ) y Cs 1-y Pb(I z Br 1-z ) at least one of 3.
3. The perovskite solar cell according to claim 1, characterized in that: The material of the electron transport layer includes C 60 , SnO2, BCP and PCBM.
4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that: The thickness of the buffer layer is 30-100 nm.
5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Disposing the hole transport layer on the surface of the transparent electrode; S2. Disposing the perovskite light absorbing layer on the surface of the hole transport layer; S3. Disposing the buffer layer on the surface of the perovskite light absorbing layer by a liquid phase method; S4. Arrange the electron transport layer and the metal electrode in sequence on the surface of the buffer layer.
6. The preparation method according to claim 5, characterized in that: In step S3, the liquid phase method includes coating a buffer layer slurry on the surface of the perovskite light absorption layer and then annealing.
7. The preparation method according to claim 6, characterized in that: The buffer layer slurry includes the inorganic nanoparticles and a dispersant.
8. The preparation method according to claim 7, characterized in that: The dispersant includes at least one of isopropyl alcohol, ethanol, water, butyl acetate and propylene glycol methyl ether acetate; and / or the concentration of the buffer layer slurry is 0.5-2 mg / mL.
9. The preparation method according to claim 6, characterized in that: The annealing temperature is 90-110° C.; and / or the annealing time is 8-12 min.
10. Application of the preparation method according to any one of claims 1 to 4 in surface photovoltaics, space photovoltaics and wearable devices.
